Perlindungan Hukum Terhadap Pura Sebagai Kawasan Suci dari Komersialisasi Budaya Berdasarkan Peraturan Gubernur Propinsi Bali Nomor 25 Tahun 2020 - Diah Gayatri Sudibya; Kade Richa Mulyawati; Kadek Dwi Gita Cahyani; Ni Luh Anggani Nata Purnami (Fakultas Hukum, Universitas Warmadewa, 2024)
Cultural diversity in each region in Indonesia has its own values ??that must be protected. One area that has a strong culture is the island of Bali. The richness and unique culture of the island of Bali is the foundation for establishing a cultural tourism concept that is based on and imbued with the Tri Hita Karana philosophy which originates from the cultural values ??and local wisdom of Sad Kerthi and is based on Balinese Taksu. The implementation of tourism based on Balinese culture must be quality oriented, so comprehensive planning is needed in accordance with the regional development vision of Bali and also oriented towards sustainability and competitiveness, which also requires tourism management standards based on Tri Hita Karana. Bali tourism is formed with a cultural tourism strategy, namely tourism that utilizes culture as its attraction. As we know, the tourist attraction of the island of Bali is its natural beauty in the form of mountains and beaches as well as various kinds of customs and culture which really attract the attention and curiosity of tourists. To develop a tourist area, cultural tourism has a big role, not only in Bali but in many regions in Indonesia, developing its culture as a tourist attraction, by utilizing the unique culture that is being developed into a tourist destination. However, the presence of tourism brings a new paradigm where culture, which was previously consumed by local people, is now being consumed by tourists. This is what is meant by “Cultural Commercialization” for tourism. Commercialization is presenting a culture such as traditional art that is not performed as is usually done in society, but is adapted to the time and purchasing power of tourists who witness it.